Modelo de otimização para avaliação de veículos leves como alternativa em frotas de compartilhamento - Rafael Freitas Funcia., Lemme (2018)
The numerous environmental challenges of the transport sector require studies that evaluate alternatives to urban mobility. In this sense, this research focuses on light duty vehicles (LDVs) for passenger transportation, proposing and applying a conceptual model to estimate the optimum composition of fleets in small-scale car sharing projects. The optimization is based on the economic perspective of the system operator. As a differential, the model introduces non-economic parameters, the perspective of other stakeholders and the evaluation of different time horizons, by applying the principle of Shared Value. The model is applied to the VAMO project, operated by Serttel and with Enel Brasil as the energy distributor. As VAMO’s focus is on 100% electric vehicles (EVs), this technology is included as the main alternative to conventional cars, along with hybrids. That way, the model can develop an alternative approach, which can be improved, serving as a basis for future studies. The application to VAMO shows that existing infrastructure and well-established propulsion technology of conventional vehicles are economic advantages of these cars and the main barriers to the electric ones. Ethanol vehicles emerge as a balanced alternative between costs and emissions, but EVs have a prominent performance in the environmental dimension, considering emissions of greenhouse gases (GHGs) and local pollutants together. The results suggest that different technologies will play a role in the transition from the LDV market to a more sustainable future for urban mobility.